If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-11-(1+11x)=-2x+51
We move all terms to the left:
-11-(1+11x)-(-2x+51)=0
We add all the numbers together, and all the variables
-(11x+1)-(-2x+51)-11=0
We get rid of parentheses
-11x+2x-1-51-11=0
We add all the numbers together, and all the variables
-9x-63=0
We move all terms containing x to the left, all other terms to the right
-9x=63
x=63/-9
x=-7
| 5x+15=-5(x+3) | | (a-4/5)=12 | | 2(w–1)+4=4(w+1) | | h=6h+3/5 | | 16=z/4 | | -0.09y+0.08(9000-y)=0.08y | | (6)6x-3=5x-10 | | 2m+3=11;3 | | 0.5t+4.1=-0.3t | | 4+3(h-2)=19 | | -7(x-2)+1=15-7x. | | 9=k+1€ | | x^2-9x-420=0 | | 1/3x6=11 | | 5a=4(3a-8)=4=13a | | 8a-5+2(a+1)=-3(a-6) | | 4x+x-8=4x+3 | | 2.7+4x-9=-6 | | Y-3(2y)=76 | | 10=10+6r | | 5a+4(3a-8=4+13a | | 144m^2-72m+9=0 | | X+25=25;x= | | -2h-10=3h+15 | | .5h+1/3(h-6)=5/6h+2 | | 9-72m+144m^2=0 | | -1/3h-10=-3 | | 4t-t=2t-19 | | x-5.5=0.2 | | 1/2x+7=30 | | 3(x+2)+7(x-3)-13=-3(x+5)-2(x-7) | | 5y+2=1/2(10y/4 |